Detecting Single Molecule Deoxyribonucleic Acid in a Cell Using a Three‐Dimensionally Integrated Nanopore. Issue 9 (15th August 2021) - Tsutsui, Makusu; Yokota, Kazumichi; Arima, Akihide; Washio, Takashi; Baba, Yoshinobu; Kawai, Tomoji
Abstract: Amplification‐free genome analysis can revolutionize biology and medicine by uncovering genetic variations among individuals. Here, the authors report on a 3D‐integrated nanopore for electrolysis to in situ detection of single‐molecule DNA in a cell by ionic current measurements. It consists of a SiO2 multipore sheet and a SiN x nanopore membrane stacked vertically on a Si wafer. Single cell lysis is demonstrated by 10 6 V m −1 ‐level electrostatic field focused at the multinanopore. The intracellular molecules are then directly detected as they move through a sensing zone, wherein the authors find telegraphic current signatures reflecting folding degrees of freedom of the millimeter‐long polynucleotides threaded through the SiN x nanopore. The present device concept may enable on‐chip single‐molecule sequencing to multi‐omics analyses at a single‐cell level. Abstract : Vertically stacked nanopore membranes enable single‐cell electrolysis to in situ intracellular biomolecule detections by ionic current measurements.